Pyogenic liver abscess in children - Duque-Estrada, Eduardo de Oliveira; Duarte, Marcelo; Ribeiro, Jones (Journal of Pediatric Infectious Diseases, 2006)
Improvements in the medical and surgical care of pediatric patients have substantially reduced the incidence of pyogenic liver abscess, which is now a very uncommon condition in children. The purpose of this study was to review five cases of pyogenic liver abscess in children presenting to our hospital. Three patients were managed by percutaneous needle aspiration under ultrasonographic guidance together with antibiotic therapy. Two patients with multiple small abscesses were managed by prolonged antimicrobial treatment alone. All five patients survived. The etiology, diagnosis and medical and surgical management of liver abscess in children are discussed.
Keywords: Liver abscess; percutaneous drainage; clinical treatment; antibiotics; children